HAMBATAN SERIKAT PEKERJA DALAM PENYELESAIANPERMASALAHAN HUBUNGAN INDUSTRIAL - Fitriyah, Fitriyah; Wardhana, Rakha Gusti (Jurnal Ilmu Kesejahteraan Sosial, 2019)
Although labore unions can help their members in solving problems related to industrial relations, it still takes a long time due to the lack of it’s ability to negotiate with companies. This can be seen in the process of resolving layoffs and work status at PT X which took 4 years, from 2013 to 2016 to reach an agreement. This research aims to describe the obstacles faced by labor unions in conducting negotiations and the efforts they have made to improve their capabilities. This research is a qualitative descriptive study and using purposive sampling techniques to selected the informant and data collection is done through in-depth interviews and literature studies. The results showed that the obstacles faced by labor unions in conducting negotiations with companies came from internal and from the company. Internal barriers are not yet the maximum function and structure of LaborUnions, lack of understanding and capacity in using bargaining strategies, lack of motivation to solve workers' problems, there are differences in interpretation among management related to negotiating material, lack of support from workers. Obstacles from the company include laying off workers and threatening workers who participated in strikes. The efforts made by the union to overcome these obstacles are forming a solid and strong negotiating team, following negotiation training conducted by the Federation of Indonesian Metal Trade Unions